The 1969 African Refugee Convention: Innovations, Misconceptions, and Omissions - Sharpe, Marina (McGill Law Journal / Revue de droit de McGill, 2012)
This paper provides a critical overview of the 1969 African refugee convention, beginning with a survey of its legal innovations. It then addresses the most misunderstood of them—the unique refugee definition—in depth, with an emphasis on dispelling the common misconception that it is particularly expansive. Finally, it investigates the 1969 Convention’s silence regarding refugees’ civil and political, and socio-economic rights, and how it works as the “regional complement” to the 1951 global refugee convention in that regard.